Zinc Oxide Suspension in Photocatalytic Oxidation of Dihydropyrimidinones - Nasr-Esfahani, M.; Montazerozohori, M. (Asian Journal of Chemistry, 2011)
Zinc oxide has been used for the photocatalytic oxidation of some ethyl 3,4-dihydropyrimidin- 2(1H)-one-5-carboxylates to their corresponding ethyl pyrimidin-2(1H)-one-5-carboxylates under UV irradiation by 400W high pressure mercury lamp in oxygen atmosphere in acetonitrile. The effects of some physicochemical parameters such as amount of photocatalyst, solvent and time of irradiation were studied. The pyrimidinone compounds were attained from the related dihydropyrimidinone after 4-8 h. The results showed the photostability of this type of compounds.